IMPLEMENTASI METODE SAW DALAM PENILAIAN KINERJA PEGAWAI ICU PADA RSPAD GATOT SOEBROTO - Muhamad Fikri Nugraha; Yuma Akbar; Dadang Iskandar Mulyana; Wahyu Saputro (Cross-border, 2021)
The company performs the best performance appraisal of employees to evaluate, motivate, verify and improve their performance. Employee performance appraisal can make it easier for leaders to assess the performance of their employees and which later the results of this performance appraisal can be used as a reference for selecting employees with good work quality. In conducting this assessment, the simple additive method (SAW) can be used. The simple method of the additive method is very helpful in ranking to determine the assessment of employee performance. In the intensive care unit (ICU) itself, currently evaluating the performance of its employees using the SAW methode.